Positive Treatment Expectations Shape Perceived Medication Efficacy in a Translational Placebo Paradigm for the Gut-Brain Axis - Benson, Sven; Theysohn, Nina; Kleine-Borgmann, Julian; Rebernik, Laura; Icenhour, Adriane; Elsenbruch, Sigrid (Frontiers in Psychiatry, 2022)
Placebo research has established the pivotal role of treatment expectations in shaping symptom experience and patient-reported treatment outcomes. Perceived treatment efficacy constitutes a relevant yet understudied aspect, especially in the context of the gut-brain axis with visceral pain as key symptom. Using a clinically-relevant experimental model of visceral pain, we elucidated effects of pre-treatment expectations on post-treatment perceived treatment efficacy as an indicator of treatment satisfaction in a translational placebo intervention. We implemented positive suggestions regarding intravenous treatment with a spasmolytic drug (in reality saline), herein applied in combination with two series of individually-calibrated rectal distensions in healthy volunteers. The first series used distension pressures inducing pain (pain phase). In the second series, pressures were surreptitiously reduced, modelling pain relief (pain relief phase). Using visual analogue scales (VAS), expected and perceived treatment efficacy were assessed, along with perceived pain intensity. Manipulation checks supported that the induction of positive pre-treatment expectations and the modelling of pain relief were successful. Generalized Linear Models (GLM) were implemented to assess the role of inter-individual variability in positive pre-treatment expectations in perceived treatment efficacy and pain perception. GLM indicated no association between pre-treatment expectations and perceived treatment efficacy or perceived pain for the pain phase. For the relief phase, pre-treatment expectations (p=.024) as well as efficacy ratings assessed after the preceding pain phase (p<.001) were significantly associated with treatment efficacy assessed after the relief phase, together explaining 54% of the variance in perceived treatment efficacy. The association between pre-treatment expectations and perceived pain approached significance (p=.057) in the relief phase. Our data from an experimental translational placebo intervention in visceral pain support that reported post-treatment medication efficacy is shaped by pre-treatment expectations. The observation that individuals with higher positive expectations reported less pain and higher treatment satisfaction after pain relief may provide first evidence that perceived symptom improvement may facilitate treatment satisfaction. The immediate experience of symptoms within a given psychosocial treatment context may dynamically change perceptions about treatment, with implications for treatment satisfaction, compliance and adherence of patients with conditions of the gut-brain axis.